2012
DOI: 10.1177/1088357611428333
|View full text |Cite
|
Sign up to set email alerts
|

Bicycle Training for Youth With Down Syndrome and Autism Spectrum Disorders

Abstract: Children with Down syndrome (DS) and autism spectrum disorders (ASD) frequently have difficulty riding a two-wheel bicycle. The purpose of this study was to investigate an intervention using an adapted bicycle and individualized instruction to teach 71 youth to ride a standard two-wheel bicycle. Youth with DS (n = 30) and ASD (n = 41) between the ages of nine and 18 years took part in this study. After five days of training, 73.3% of children with DS and 85.4% with ASD successfully demonstrated the ability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 25 publications
2
49
0
Order By: Relevance
“…Even at a young age, the motor skill deficits of children with ASD widen as the children become older (age range 14–36 months) (Lloyd, et al, 2013). Teaching motor skills to children with ASD, through adapted physical activity, has been successful (MacDonald et al, 2012). How to best implement motor skill improvements for young children with ASA and how to combine early intervention to include motor skill development is an area of future research.…”
Section: Discussionmentioning
confidence: 99%
“…Even at a young age, the motor skill deficits of children with ASD widen as the children become older (age range 14–36 months) (Lloyd, et al, 2013). Teaching motor skills to children with ASD, through adapted physical activity, has been successful (MacDonald et al, 2012). How to best implement motor skill improvements for young children with ASA and how to combine early intervention to include motor skill development is an area of future research.…”
Section: Discussionmentioning
confidence: 99%
“…MacDonald and friends [13] applied individualized education method to children at at cycling upskilling study carried out with 30 individual with down syndrome and 41 individuals with autism. It was observed that 73.3% of children with down syndrome and 85.4% of children with autism could cycle for a distance longer than 100 meters at the end of 5 days of study.…”
Section: Discussionmentioning
confidence: 99%
“…In respect of teaching disabled people to ride, Klein et al (2005) report a methodology which includes innovative teaching techniques and specialised equipment. MacDonald et al (2012) investigated the effect of a cycle training intervention for children with Down's Syndrome (DS) and autism spectrum disorders (ASD).…”
Section: 2mentioning
confidence: 99%